PENGEMBANGANNLEMBARNKERJANPESERTANDIDIK (LKPD) BERBASISSPENDEKATAN SAINTIFIKNDALAMNBELAJARNSENI RUPA KELAS XII DI SMAN 7 PADANG - Drs. Wisdiarman, M.Pd., DINI IQDATUL HAKIKI, (Serupa The Journal of Art Education, 2021)
Oneoof thellearning tools thatmmust beeprepared before teaching is the Student Worksheet (LKPD). The 2013 curriculum mandates that the.implementation.of learning must be based on the Scientific Approach, including in developing LKPD. However, at this time fine arts learning in SMA has not yet used LKPD based on the Scientific Approach. This study aims to develop LKPD for learning fine arts based on a scientific approach that is suitable for use in high school, so that it can improve students' abilities inaaccordance withhtheddemands of the 2013 curriculum. This research is a development research that refers to the 4-D model development model, namely define, design, develop, and disseminate (Thiagarajan, Sivasailam, in Trianto, 2009). While the quality of the Student Worksheet (LKPD) to be described includes the feasibility of the LKPD from the experts and the responses from teachers and students. The instruments used in this study were validation sheets for experts and teacher and student response questionnaires. The results showed that the LKPD based on the Scientific Approach developed for fine arts subjects in class XII SMA had met the valid criteria in terms of approach, content / material, presentation, language and graphics. Thus, it can be concluded that the LKPD based on the Scientific Approach developed for fine arts subjects is valid and practical. So it is ready for large-scale trials in class XII SMA.Keywords: Student Activity Sheet (LKPD), Scientific Approach.